PENGARUH TERAPI MUSIK TERHADAP PENURUNAN TEKANAN DARAH PADA PASIEN POST HEMODIALISA DI RSUD PROF. DR. MARGONO SOEKARJO PURWOKERTO - Catur Sayekti; Rahmaya Nova Handayani; Suci Khasanah (Viva Medika, 2015)
One of hemodialisa complication is the increase of blood pressure. Some of research show that music therapy can decrease blood pressure. The purpose is to know the influence of music therapy to thedecrease of blood pressure in post hemodialisa patients. Research design is quasy eksperiment designnon equivalent control group. Sampling technique is purposive sampling. The sample of the researchwere 20 respondents (as control group, and experiment group). The data taken measurement of bloodpressure before and after music therapy. The analysis used are difference test and logistic regression.The results show that there is difference sistolik of blood pressure on the experiment group and thereisn’t difference on the control group ((p = 0,001 < 0,05) , (p = 0,180 > 0,05)), there isn’t differencediastolik of blood pressure on the experiment group and there isn’t difference on the control group ((p =0,343 > 0,05), (p = infinite)), there isn’t difference sistolik of blood pressure before and after betwe enexperiment group with control group (p = 0,175 > 0,05), (p = 0,055), there isn’t difference diastolik ofblood pressure before and after between experiment group with control group ((p = 0,231 > 0,05), (p =0,299 > 0,05)), there is relationship sistolik of blood pressure on hemodialisa patients, how manyinfluence can’t presumably because OR can’t uncountable (p = 0,000, OR uncountable). The result ofthis research shows there is not the influence of music therapy to the decrease of blood pressure in posthemodialisa patients. Keywords: Music therapy, blood pressure